Role of Fathers in developing Career Adapt-abilities among Emerging Adults - Anwar, Nida; Mushtaq, Rabia; Alyana, Sajid Iqbal (Annals of Human and Social Sciences, 2024)
This study investigates the relationship between perceived paternal parenting practices and the career development abilities of emerging adults. Specifically, it investigates how emerging adults’ career adaptabilities of curiosity and confidence relate to perceived paternal autonomy support, involvement, and warmth. After an in-depth review of the existing literature following hypothesis was formulated for this study. Perceived paternal parenting practices (i.e., perceived paternal autonomy support, involvement, and warmth) would be significant predictor of career adopt-capacities (i.e., curiosity & confidence) in emerging adults. 370 emerging adults (220 male & 150 female) were taken from private and public universities of Faisalabad, Pakistan in the age range of (18 to 25 years) using Purposive Sampling. Besides a Demographic Form, Perceptions of Parents Scales; (The College- Student Scale) and The Career Adapt- Abilities Scale were administered. The Multiple Regression Analyses was used to test the hypotheses of the study. Result revealed that Perceived paternal parenting practices (i.e., perceived paternal autonomy support, involvement, and warmth) is a significant predictor of career adopt-capacities (i.e., curiosity & confidence) in emerging adults. It has been shown that supportive networks can help individuals navigate these and move into a more successful career. The findings stressed upon the importance of specific paternal parenting practices for adolescents’ career adapt- abilities. The findings have important implications and can be used in future researches as guidance.